Reasons for refusing orthognathic surgery by orthodontic patients: a cross-sectional survey - Jawaid, Mazia; Ahsan Qadeer, Tabassum; Fahim, Muhammad Faisal (Journal of the Pakistan Medical Association, 2022)
Objectives: To find out the most common reasons for refusing orthognathic surgery and to compare the responses along gender lines and in terms of open-ended and closed-ended approaches. Method: The cross-sectional retrospective study was conducted from August to December 2020 at the Orthodontics Department of Bahria University Medical and Dental College, Karachi, Pakistan, and comprised of patients who were planned for but refused orthognathic surgical treatment between January 2018 and July 2020. Data was collected through telephone-based interviews to record reasons of avoiding orthognathic surgery. The data-collection tool had both open-ended and closed-ended questions. Data was analysed using SPSS 23. Results: Of the 60 patients, 42(70%) were females and 18(30%) were males with a mean age range of 23.25±2.19years. Overall, 19(31.7%) patients avoided surgery due to additional expense, while post-operative pain was cited as a reason by 35(58.3%) patients. Males were 9 times more concerned about their dental alignment compared to females (p=0.005). Fear of tooth injury (p<0.0001) and intra-operation and post-operation bleeding (p<0.0001) were found twice in males than females. Conclusion: The most common reasons for refusal to have orthognathic surgery were increased cost and post-operative pain. Males were more concerned about dental alignment and had higher fear of post-surgical tooth injury and intra- and post-operative bleeding compared to the females. Key Words: Orthognathic surgery, Maxillo-mandibular surgery, Jaw abnormalities, Intraoperative complications, Post-operative complications, Post-surgical pain, Haemorrhage.